Histopathological and immunohistochemical parameters of breast cancer cases analyzed in a reference laboratory - Soares, Marina Crespo; Rodrigues, Isabela Juliana Manfredo; Almeida, Igor Cerejo Tavares da Silva de; Assunção, João Victor Pereira; Monteiro, Andrew Moraes; Dias Júnior, Leônidas Braga (Mastology, 2020)
Objective: To determine the histopathological and immunohistochemical parameters of breast cancer cases treated in Belém, state of Pará, Brazil. Method: This is a cross-sectional, retrospective and observational study in which samples from 278 patients were analyzed. In the histopathological analysis were considered, among other factors, the differentiation and histopathological classification of the tumor, based on the WHO classification. As for immunohistochemistry, the presence and intensity of expression of the cell proliferation antigen Ki-67, gene product of HER2, and estrogen and progesterone receptors were evaluated. Then, the tumors were classified into luminal A, luminal B, luminal hybrid, HER2 group, and basal-like. Results: The most common histological subtypes were invasive carcinoma of no special type (88.7%), carcinoma in situ (5.5%), and invasive mucinous carcinoma (2.9%). The most common immunohistochemical subtypes were luminal A (26.1%), basal-like (23.6%), and luminal B (23.2%). We also found a statistically significant inversely proportional relationship (p<0.01) of hormone receptor expression with nuclear grade. Conclusion: The results show the importance of immunohistochemical analysis for staging, as well as for the therapeutic decision of each patient. However, further studies with a larger sample must be performed for more effective analysis of the general population.